Mikoriza Rhizoctonia : Sebagai Agen Ketahanan Pada Anggrek Dendrobium - Soelistijono, R.; Supriyadi, Teguh; Tiara Maharani, Annissa; Imani Fatihah, Syalaysa (JURNAL ILMIAH AGRINECA, 2025)
Drought and low rainfall are natural phenomena that occurred in 2022-2023. These factors (abiotic factors) caused diseases in orchids, which affect the metabolism of growth and the flowering process, making the plants unable to survive in their habitat because they cannot reproduce, thus classifying them under Appendix 2 (CITES). However, some orchid species that are endemic are able to withstand drought and low rainfall. It is suspected that the orchids' ability to endure these factors is due to the role of endophytic fungi (Rhizoctonia binucleate / BNR), which can associate with orchids and produce secondary metabolites that help supply nutrients to the orchids during drought stress. This study aims to evaluate the biological resistance of different strains of Rhizoctonia binucleate / BNR isolates in Dendrobium orchids to understand their impact on water stress. The research method used a completely randomized design with a single stage consisting of two factors and five replications. Factor 1: orchid seedling types consisting of S1 = Phalaenopsis violaceae (epiphytic orchid) and S2 = Dendrobium aggregatum (epiphytic orchid). Factor 2: types of Rhizoctonia mycorrhiza application consisting of K0 = control, K1 = Rhizoctonia mycorrhiza application.